STRUKTUR POPULASI DAN NATURAL INCREASE KAMBING LOKAL GORONTALO DI KECAMATAN BOTUPINGGE PROVINSI GORONTALO - Ilham, Fahrul; Sayuti, Muhammad; Isa, Arman; Zainudin, Srisukmawati (Jambura Journal of Tropical Livestock Science, 2023)
This research aims to identify the population structure and natural increase of local Gorontalo goats in Botupingge District, Bone Bolango Regency, Gorontalo. The total number of local Gorontalo goats observed at the research location was 163. The research method is by survey and data collection by observation and interviews using a list of questions. The research results showed that the number of local goats at the time of the research was 126 females and 37 males. The population structure consists of 7 adult males (18.91%) and 77 adult females (61.11%), seven young males (18.91%) and 26 young females (20.63%), male offspring 23 (62.16%) and 23 (18.69%) female offspring. The population structure of unsex goats is 28.22%, young goats are 20.24%, and adult goats are 51.53%. The highest import of goat livestock into the Botupingge District area was caused by births (81.81%), and expenditure was caused by deaths and sales (43.66%). The percentage of births to adult parents is 70.12%, and to the total population is 33.12%, purchases 16.66%, and immigration 1.51%. The percentage of goat deaths in the population was 19.01%, sales were 19.01%, slaughter was 4.29%, and natural increase was 14.11%. This research concludes that adult goats with female gender dominate the population structure of local Gorontalo goats in Botupingge District. However, when they are still young, they are dominated by male goats. The natural increase in local Gorontalo goats is 14.11% and is in the small/low category, so strategic breeding efforts are needed to reduce deaths and increase births